Night Vision(s) ... - Duxbury, Lesley (RMIT University, 2024)
BACKGROUND: Artists have long responded to and interpreted the work of other artists. The current British Council project through which significant writers and poets have been invited to respond to Shakespeare's works on the 400th anniversary of his death. This group exhibition curated by Dr Felicity Spear drew together 9 artists with interests in the sky and astronomy to reveal their diverse responses to a complex yet fictional story, Somnium or The Dream, by Johannes Kepler, the 17th century German mathemetician and astronomer. CONTRIBUTION: The motivation for Duxbury's Night Vision(s) was the photographs she took of the Aurora Borealis while on an artist residency in North Iceland in October 2015. These along with the introductory text in Kepler's Somnium led her to reflect on her dream-like experiences of the Aurora in such a volatile location. The Aurora Borealis flitters across the sky in spooky, magical bands and waves reminiscent of the spirits recounted by the mother in Somnium, who "reject the ...